2011
DOI: 10.1002/rcm.5083
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of deprotonated microcystin variants by collision‐induced dissociation following electrospray ionization

Abstract: Microcystins (MC) are a family of hepatotoxic cyclic heptapeptides produced by a number of different cyanobacterial species. Considering the recent advances in the characterization of deprotonated peptides by mass spectrometry, the fragmentation behavior of four structurally related microcystin compounds was investigated using collision-induced dissociation (CID) experiments on an orbitrap mass spectrometer. It is demonstrated in this study that significant structural information can be obtained from the CID s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Negative ionization mode by MALDI and ESI presented low absolute intensities but also low background and therefore provided suitable S/N ratios. According to other authors [19][20][21]44], as shown Table S1 of supplementary data, the analysis of MCs containing no Arg residue such as MC-LA, -LF, -LW and -LY presented high sensitivity in negative ionization mode.…”
Section: Throughput Analysis (Direct Maldi and Esi Analysis)mentioning
confidence: 96%
See 3 more Smart Citations
“…Negative ionization mode by MALDI and ESI presented low absolute intensities but also low background and therefore provided suitable S/N ratios. According to other authors [19][20][21]44], as shown Table S1 of supplementary data, the analysis of MCs containing no Arg residue such as MC-LA, -LF, -LW and -LY presented high sensitivity in negative ionization mode.…”
Section: Throughput Analysis (Direct Maldi and Esi Analysis)mentioning
confidence: 96%
“…The main fragment ions of MC-LR have been included in Table 2. These fragment ions have been already described in the literature [19,21,52] but in the present manuscript all the fragment ions have been evaluated for confirmatory purposes. As shown in Fig.…”
Section: Tablementioning
confidence: 98%
See 2 more Smart Citations
“…Single [MþH] þ and double charged [Mþ2H] 2þ ions are frequently observed in the positive mode, especially for variants containing basic arginine residues, such as MC-RR (Dörr et al, 2010). However, recently, Dörr et al (2011) presented an extensive study with the mass spectra characterization of several microcystins after negative electrospray ionization and Gambaro et al (2012) presented a negative ionization electrospray quantitative method, using liquid chromatography coupled to a triple quadrupole, applied to aerosol samples from Venice Lagoon, reaching detection limits of 1 ng/L. This work presents the development and application of an analytical LC/ESI/MS 2 ion trap method, using the negative ionization mode, which can be used as a sensitive and accurate tool for the characterization of environmental and health risks due to cyanotoxins.…”
Section: Introductionmentioning
confidence: 98%